Mycobacterium leprae Activates Toll-Like Receptor-4 Signaling and Expression on Macrophages Depending on Previous Bacillus Calmette-Guerin Vaccination - Polycarpou, Anastasia; Holland, Martin J.; Karageorgiou, Ioannis; Eddaoudi, Ayad; Walker, Stephen L.; Willcocks, Sam; Lockwood, Diana N. J. (Frontiers in Cellular and Infection Microbiology, 2016)
Toll-like receptor (TLR)-1 and TLR2 have been shown to be receptors for Mycobacterium leprae (M. leprae), yet it is unclear whether M. leprae can signal through alternative TLRs. Other mycobacterial species possess ligands for TLR4 and genetic association studies in human populations suggest that people with TLR4 polymorphisms may be protected against leprosy. Using human embryonic kidney-293 cells co-transfected with TLR4, we demonstrate that M. leprae activates TLR4. We used human macrophages to show that M. leprae stimulation of cytokine production is diminished if pre-treated with TLR4 neutralizing antibody. TLR4 protein expression was up-regulated on macrophages derived from non-bacillus Calmette-Guerin (BCG) vaccinated healthy volunteers after incubation with M. leprae, whereas it was down-regulated in macrophages derived from BCG-vaccinated donors. This may be related to vaccination induced epigenetic changes similar to those attributed to lipopolysaccharide-induced tolerance or trained immunity in human macrophages. Finally, pre-treatment of macrophages derived from BCG-naive donors with BCG reversed the effect of M. leprae on TLR4 expression. This may be a newly described phenomenon by which BCG vaccination stimulates ‘non-specific’ protection to the human immune system.